Expression of the Multidrug Resistance Transporter NorA from Staphylococcus aureus Is Modified by a Two-Component Regulatory System - Fournier, Bénédicte (American Society for Microbiology, 2000)
To dissect genetically the regulation of NorA, a multidrug transporter of Staphylococcus aureus, we analyzed the differential expression of the norA promoter using a transcriptional fusion with a β-lactamase reporter gene. Expression studies with an arlS mutant revealed that the norA promoter is ArlS dependent. The arlR-arlS locus was shown to code for a two-component regulatory system. The protein ArlR has strong similarity to response regulators, and ArlS has strong similarity to protein histidine kinases. We have also analyzed the 350-bp region upstream of the Shine-Dalgarno sequence of norA by gel mobility shift experiments. It was shown that only the 115-bp region upstream of the promoter was necessary for multiple binding of an 18-kDa protein. From transcriptional fusions, we have localized four different putative boxes of 6 bp, which appear to play a role in the binding of the 18-kDa protein and in the up-regulation of norA expression in the presence of the arlS mutation. Furthermore, the gel mobility shift of the 18-kDa protein was modified in the presence of the arlS mutation, and the arlS mutation altered the growth-phase regulation of NorA. These results indicate that expression of norA is modified by a two-component regulatory system.